Leadership Style, Organizational Culture, and Competence as Predictors of Employee Performance in Baubau’s Education, Youth, and Sports Department - Muhammad Ali Masyhar; Endah Andayani; Kristina Sedyastuti (Economics and Digital Business Review, 2026)
This study examines leadership style, organizational culture, and competence as predictors of employee performance at the Department of Education, Youth, and Sports of Baubau City. A quantitative explanatory design was employed involving all 65 civil servants as respondents through saturated sampling. Data were collected using a structured five-point Likert-scale questionnaire and analyzed with multiple linear regression using IBM SPSS Statistics. The results show that leadership style, organizational culture, and competence jointly form a significant model of employee performance, F(3,61) = 62.536, p < .001, explaining 75.5% of the variance in performance (R² = .755; adjusted R² = .743). Individually, leadership style (β = .067, p = .476) and organizational culture (β = .067, p = .518) do not significantly predict employee performance. In contrast, competence has a positive and significant contribution (β = .797, p < .001) and emerges as the strongest predictor. These findings indicate that improving employee performance should prioritize competence development, particularly knowledge, skills, adaptability, work attitudes, and continuous learning, while leadership and organizational culture remain important organizational supports.